(untitled) (Plant Tissue Culture and Biotechnology, 2010)
The combined role of carbohydrate and auxin is effective in root formation of date palm somatic embryos. The best combination resulted a mean of 2.5 roots per embryo and reached up to ten good and healthy roots when the rooting medium containing 60 g/l sucrose supplemented with NAA was used. 60 g/l sucrose combined with 0.4, 0.6 and 0.8 mg/l of either NAA or IBA gave about 74% root thickness. IBA with a low sucrose concentration of 30 g/l promoted root length, while NAA was found to be superior over IBA, when a high concentration of sucrose of 60 g/l was used which may be due to the effect of NAA is on the main root while IBA on the lateral root. Key words: Auxins, Rooting, Combined effect, Date palm, Somatic embryos D.O.I. 10.3329/ptcb.v19i2.5429 Plant Tissue Cult. & Biotech. 19(2): 127-132, 2009 (December)